The Contemporary EU's Notion of Territoriality and External Borders - Vitale, Alessandro (European Spatial Research and Policy, 2011)
The predominant spatial conception of the EU contributes to an evident emergence of a sharpened territorial building of the European space. By all evidence the idea of both the territorial cohesion and territorial continuity shows how relevant the notion of territoriality in the ‘European discourse’ is and consequently how accepted the instrument of hard and closed border and the sharp inside/outside dichotomy are. Due to this pragmatic notion of territoriality, the idea of the EU as a ‘non-Westphalian new empire’ (according to the ‘neo-medieval paradigm’) became at least unrealistic. Its borders are getting more territorial, physical and visible. Hard border policies and practices on the Eastern and Western Balkan borders mirror the existence of a de facto barrier and of a deep ‘Westphalian memory’ in the way of using the territory as support of political unity.